Bovine Neonatal Pancytopenia-Associated Alloantibodies Recognize Individual Bovine Leukocyte Antigen 1 Alleles - Kasonta, Rahel; Mauritz, Jacqueline; Spohr, Christina; Sauter-Louis, Carola; Duchow, Karin; Cussler, Klaus; Holsteg, Mark; Bastian, Max (Frontiers in Immunology, 2018)
Bovine Neonatal Pancytopenia (BNP) was a vaccine induced alloimmune disease observed in young calves and characterized by haemorrhages, pancytopenia and severe destruction of the hematopoietic tissues. BNP was induced by alloreactive maternal antibodies present in the colostrum of certain cows vaccinated with a highly adjuvanted vaccine against Bovine Viral Diarrhoea. Bioprocess impurities, originating from the production cell line of the vaccine, are likely to have induced these alloreactive antibodies. One prominent alloantigen recognized by vaccine induced alloantibodies is highly polymorphic bovine MHC-I (BoLA I). Aim of this study was to define the fine specificity of BNP-associated anti-BoLA I alloantibodies. In total, eight different BoLA I alleles from the production cell line were identified. All genes were cloned and recombinantly expressed in murine cell lines. Using these cells in a flow cytometric assay the presence of BoLA I specific alloantibodies in BNP dam sera was proven. Three BoLA I variants were identified that accounted for the majority of vaccine induced BoLA I reactivity. By comparing the sequence of immunogenic to non-immunogenic BoLA I variants probable minimal epitopes on BoLA I were identified. In general, dams of BNP calves displayed high levels of BoLA I reactive alloantibodies, while vaccinated cows delivering healthy calves had significantly lower alloantibody titres. We identified a subgroup of vaccinated cows with healthy calves displaying very high alloantibody titres. Between these cows and BNP dams no principle difference in the BoLA I reactivity pattern was observed. However, with a limited set of dam-calf pairs it could be demonstrated that serum from these cows did not bind to BoLA I expressing leukocytes of their offspring. By contrast, when testing cells from surviving BNP calves with the corresponding dam’s serum there was significant binding. We therefore conclude that predominantly highly alloreactive cows are at risk to induce BNP and it depends on the paternally inherited BoLA I whether or not the calf develops BNP.